Corruption and Underdevelopment in Nepal: A Content Analysis - Ghimire, Dipesh Kumar (Dhaulagiri Journal of Sociology and Anthropology, 2022)
Many studies show that corruption negatively affects public investment, reduces government revenue, misuses public resources, and decreases expenditure and quality of life for the people. It is also considered the leading cause behind the low quality of infrastructure, damaging social, economic, political, and infrastructural development. Similarly, corruption also hinders development because it distorts resources affecting economic growth and service delivery. So, corruption and underdevelopment have a positive correlation. Corruption has been a major driving force behind underdevelopment in many countries. This article is written based on secondary data. The content of news published in newspapers was analyzed during the study. This paper reveals the prevalence of high levels of corruption in the governance system and development activities is the main reason behind the underdevelopment in Nepal.